Total liquid ventilation offers ultra-fast and whole-body cooling in large animals in physiological conditions and during cardiac arrest. (August 2015) - Hutin, Alice; Lidouren, Fanny; Kohlhauer, Matthias; Lotteau, Luc; Seemann, Aurélien; Mongardon, Nicolas; Renaud, Bertrand; Isabey, Daniel; Carli, Pierre; Vivien, Benoit; Ricard, Jean-Damien; Hauet, Thierry; et al.
Abstract: Introduction: Total liquid ventilation (TLV) can cool down the entire body within 10–15 min in small animals. Our goal was to determine whether it could also induce ultra-fast and whole-body cooling in large animals using a specifically dedicated liquid ventilator. Cooling efficiency was evaluated under physiological conditions (beating-heart) and during cardiac arrest with automated chest compressions (CC, intra-arrest). Methods: In a first set of experiments, beating-heart pigs were randomly submitted to conventional mechanical ventilation or hypothermic TLV with perfluoro-N-octane (between 15 and 32 °C). In a second set of experiments, pigs were submitted to ventricular fibrillation and CC. One group underwent continuous CC with asynchronous conventional ventilation (Control group). The other group was switched to TLV while pursuing CC for the investigation of cooling capacities and potential effects on cardiac massage efficiency. Results: Under physiological conditions, TLV significantly decreased the entire body temperatures below 34 °C within only 10 min. As examples, cooling rates averaged 0.54 and 0.94 °C/min in rectum and esophageous, respectively. During cardiac arrest, TLV did not alter CC efficiency and cooled the entire body below 34 °C within 20 min, the low-flow period slowing cooling during CC. Conclusion: Using a specifically designed liquid ventilator, TLV induced a very rapid cooling of the entire body in large animals. This was confirmed in both physiological conditions and during cardiac arrest with CC. TLV could be relevant for ultra-rapid cooling independently of body weight.